Development of Green Entrepreneurship Based on Urban Farming to Create Environmentally Friendly Dense Cities - Zulkarnain Nasution; Hamdi Hamdi; Siswa Panjang Hernosa (Randwick International of Social Science Journal, 2026)
This study aims to analyze the influence of urban space utilization and the use of environmentally friendly technology on the development of urban farming and its impact on food security in Medan City. Rapid urbanization has led to limited land and increasing food needs in urban areas. Urban farming is seen as an innovative solution through the use of limited space and technologies such as hydroponics and vertical farming. This study also assesses the role of community participation as a moderation variable in strengthening the relationship between space utilization, environmentally friendly technology, and food security. The results of the study are expected to provide strategic recommendations for the development of green entrepreneurship and sustainable improvement of urban food security. This study uses the Systematic Literature Review (SLR) approach with the guidance of PRISMA to examine the concept of smart urban farming based on herbal probiotics in the economic empowerment of urban communities. The literature for 2015–2024 is analyzed through the stages of identification, selection, feasibility assessment, and data synthesis to produce a conceptual framework and recommendations for implementation in the city of Medan in a sustainable manner. Based on the study conducted, the use of urban space and the use of environmentally friendly technology have an important role in the development of urban farming as a form of green entrepreneurship in the city of Medan. Optimal use of space allows for the creation of productive land in the midst of urban limitations, while environmentally friendly technology improves production efficiency and agricultural sustainability. Simultaneously, these two factors contribute to increasing community food security. In addition, community participation has proven to be an important factor that not only affects food security directly, but also strengthens the influence of space utilization and environmentally friendly technology in supporting the success of sustainable urban farming.